Electromyographic study of the longissimus dorsi and iliocostalis lumborum muscles during knee flexion and extension on a plain and on a tilt Roman table - Masselli, M. R. [UNESP]; de Camargo, A. M.; Bérzin, F. (Electromyogr Clin Neurophysiol, 1994)
The objective of this paper was to analyse the activity of the longissimus dorsi and the iliocostalis lumborum muscles--components of the erector spinae muscle--in order to determine: their action potentials during the use of a plain and a tilt Roman table; 2) to compare the action potentials of the two muscles; 3) to verify if the action potential of these two muscles remain constant during the arc of movement--knee flexion and extension--divided into angle ranges, and 4) to compare the action potentials of the muscles in movements performed in a free manner and against resistance. Twenty-three young volunteers were studied electromyographically and each muscle received a needle electrode (Mise) and a surface electrode. The results showed that the table model did not determine any difference in the action potential of the muscles and that, on average, the iliocostalis lumborum muscle developed a slightly higher action potential than the longissimus dorsi muscle during the free flexion of knees on the plain table. In more than 70% of the cases, there was no difference between the action potential of the muscles over the various angle ranges of knee flexion and extension. Relatively higher action potentials were recorded during knee flexion and extension against resistance than during the same movements performed in a free manner. This shows that the paravertebral musculature responds better to an overload (8 kg) imposed on the knee flexor group, confirming the stabilizing role of the longissimus dorsi and iliocostalis lumborum muscles during knee flexion and extension on a Roman table.